2020
DOI: 10.1136/bmjresp-2019-000488
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators for in-hospital mortality in COPD with acute exacerbation in Thailand: a retrospective cohort study

Abstract: BackgroundAcute exacerbation of chronic obstructive pulmonary disease (AECOPD) is a common and deteriorating event leading to in-hospital morbidity and mortality. Identification of predictors for in-hospital mortality of AECOPD patients could aid clinicians in identifying patients with a higher risk of death during their hospitalisation.ObjectiveTo explore potential prognostic indicators associated with in-hospital mortality of AECOPD patients.SettingGeneral medical ward and medical intensive care unit of a un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…Consistent with previously reported studies on mortality in AECOPD, advanced age was recognized as a significant predictor for mortality in our study ( 18 , 20 ). Respiratory failure emerged as a strong risk factor for in-hospital mortality, which is similar to a recent research on hypercapnia during respiratory failure increased the risk of mortality ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previously reported studies on mortality in AECOPD, advanced age was recognized as a significant predictor for mortality in our study ( 18 , 20 ). Respiratory failure emerged as a strong risk factor for in-hospital mortality, which is similar to a recent research on hypercapnia during respiratory failure increased the risk of mortality ( 21 , 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Respiratory failure emerged as a strong risk factor for in-hospital mortality, which is similar to a recent research on hypercapnia during respiratory failure increased the risk of mortality ( 21 , 22 ). The increase in mortality risk was also observed in patients with respiratory failure in a cohort in Thailand ( 20 ). Respiratory failure is a serious complication in severe exacerbations.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Kim et al showed that, after grouping the population by age quartiles, the rate of FEV1 decline was faster among older patients than younger ones [ 43 ]. Other studies have also shown that COPD patients had higher odds of inpatient mortality and morbidity, particularly if they were more than 80 years of age [ 44 , 45 ]. So, we included age in the logistic regression as a confounder.…”
Section: Discussionmentioning
confidence: 99%
“…Second, an arterial puncture was also required for the evaluation of acidemia. In Thailand, blood gas analysis was only performed in patients with AECOPD who were intubated and needed regular ventilation adjustment [20]. Thus, for patients with AECOPD without acute respiratory failure, blood gas analysis was not generally available for the calculation of the DECAF score.…”
Section: Introductionmentioning
confidence: 99%